Studying the kinetic energy budget and moisture transport during a severe case of cyclogenesis - Abdulhaleem H. Labban (Applied Water Science)
Abstract This work aimed to investigate the kinetic energy budget and moisture transport of a case of cyclogenesis that causes intense rains over north and middle parts of Saudi Arabia on November 23–25, 2022. The study of kinetic energy (KE) and its budget concludes that the majority of the KE was concentrated at 400 hPa and above, coinciding with the powerful activity of the subtropical jet stream during the period of cyclogenesis. The KE generation through cross-contour flow serves as a major energy source. During the cyclogenesis process, KE dissipation from grid to subgrid scales is a major energy sink, while the horizontal flux divergence of KE acts as a source of KE. The study of moisture transport through the attributes of moisture-flux components and the dispersion of perceptible water during the cyclogenesis reveals that within the lower tropospheric layer, the rotating component of moisture flux brings moisture from two primary regions: One zone spans the Arabian Sea and includes the south Red Sea, north of Ethiopia, and central Sudan; the other region covers the Mediterranean Sea and the North Atlantic. The primary moisture source in the middle layer is located over central Africa, with origins traced back to the Atlantic Ocean, Arabian Sea, and Indian Ocean.